Hydrogeology Potential of Hargorejo Area Kokap Subdistrict West Progo Regency - T. Listyani R.A.; Dianto Isnawan; Ign. Adi Prabowo (Institut Teknologi Dirgantara Adisutjipto, 2020)
This research is a hydrogeological survey activity with the aim to determine the geological characteristics of groundwater in the Hargorejo area, Kokap Sub-district, West Progo. The study wants to know about the pattern of groundwater flow and water quality in the area. The northern part of the research area is included in the non-groundwater basin region of the West Progo Dome, while the southern part is included in Wates Groundwater Basin. Method of research is a field hydrogeological survey, to obtain geological and groundwater data. Groundwater flow pattern and quality analyses are based on groundwater data and pH, TDS and EC values. Groundwater can be obtained from springs or dug wells, with relatively shallow groundwater tables. The pattern of groundwater flow is generally to the south, with the H4 / H5 basin boundary type. Groundwater quality is quite good, with a pH value of 6.2 -7; TDS 191 - 558 ppm, and EC ranges from 279-783 ÂµS / cm.